TINGKAT PENGETAHUAN DAN MOTIVASI PETANI DALAM BERCOCOK TANAM NILAM DI DESA LEREPAKO KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Arjun Arjun; Dasmin Sidu; Mardin Mardin (Universitas Halu Oleo, 2022)
This study aims to: (1) determine the level of knowledge of farmers in patchouli cultivation, (2) determine the types of motivation in patchouli cultivation, (3) determine the income of farmers in patchouli cultivation. This research was conducted in Lerepako Village, Laeya District, South Konawe Regency which was carried out from July 2021 to September 2021 with a total of 20 respondents selected by census. Data analysis in this study used a descriptive method. The results of this study indicate that (1) The level of knowledge of farmers in Lerepako Village in patchouli cultivation, all farmers are already at the level of knowledge of evaluating and some farmers are already at the level of knowledge of creating. (2) The motivation of farmers in patchouli cultivation in Lerepako Village is divided into two types of motivation, namely intrinsic motivation and extrinsic motivation, intrinsic motivation is dominated by fulfilling economic needs and interest in work while extrinsic motivation is dominated by price and a soil condition with a percentage. (3) The average income of farmers in patchouli cultivation in Lerepako Village, Laeya District, Konawe Selatan Regency from patchouli oil income is Rp. 61,445,000/planting season.